Urban Pediatric Adiposity and Lifestyle Transitions: A Longitudinal Appraisal of Dietary and Metabolic Correlates Among Schoolchildren in Srinagar, Kashmir, India - Shah Fahad Firdos (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Childhood obesity has emerged as a formidable public health challenge globally, with a marked surge in prevalence across urban populations of low- and middle-income countries, including India. Amidst the nutritional transition driven by urbanization, lifestyle shifts among children—especially increased consumption of energy-dense processed foods and reduced physical activity—warrant urgent epidemiological attention. This study aimed to longitudinally assess the impact of junk food consumption and lifestyle parameters on body mass index (BMI) and metabolic markers among school-going children aged 6–14 years in urban Srinagar, Kashmir. A prospective observational study was conducted over a 12-month period involving 100 randomly selected children from both government and private schools. Baseline and endline assessments included anthropometric measurements, structured dietary and lifestyle questionnaires, and biochemical evaluations (fasting glucose and serum cholesterol). Operational definitions adhered to CDC and WHO BMI percentile standards. Statistical analyses included descriptive statistics, paired t-tests, and correlation/regression modeling to evaluate associations between lifestyle variables and changes in BMI. At baseline, 7% of participants were classified as overweight, with none obese; by endline, overweight prevalence increased to 8%, and obesity emerged in 2%. Significant correlations were observed between frequent junk food consumption and elevated BMI percentiles (p < 0.05), as well as moderate elevations in fasting glucose and cholesterol levels in children with high dietary risk profiles. Physical activity declined marginally over the study period, while screen time increased, though these were not independently predictive of BMI changes after adjustment. The findings underscore an insidious trend of early-life weight gain and metabolic shifts, largely attributable to unhealthy dietary practices entrenched in the urban lifestyle. Comparative analysis aligns with national and regional studies affirming junk food as a primary driver of pediatric adiposity. Socioeconomic and school-type differences revealed nuanced behavioral patterns, suggesting a need for stratified intervention models. The study delineates a clear trajectory of obesity risk among urban children in Srinagar, underscoring the urgent necessity of school-based preventive strategies, parental sensitization, and policy-level regulation of obesogenic exposures. Proactive, multisectoral interventions are imperative to arrest the burgeoning epidemic of childhood obesity and its downstream health consequences.